Mosquito arbovirus survey in selected areas of Kenya: detection of insect-specific virus - Hanako Iwashita; Yukiko Higa; Kyoko Futami; Peter A. Lutiali; Sammy M. Njenga; Takeshi Nabeshima; Noboru Minakawa (Tropical Medicine and Health, 2018)
Abstract Background Many arboviral outbreaks have occurred in various locations in Kenya. Entomological surveys are suitable methods for revealing information about circulating arboviruses before human outbreaks are recognized. Therefore, mosquitoes were collected in Kenya to determine the distribution of arboviruses. Methods Various species of mosquitoes were sampled from January to July 2012 using several collection methods. Mosquito homogenates were directly tested by reverse transcription-polymerase chain reaction (RT-PCR) using various arbovirus-targeted primer pairs. Results We collected 12,569 mosquitoes. Although no human-related arboviruses were detected, Culex flavivirus (CxFV), an insect-specific arbovirus, was detected in 54 pools of 324 Culex quinquefasciatus individuals collected during the rainy season. Of these 54 positive pools, 96.3% (52/54) of the mosquitoes were collected in Busia, on the border of western Kenya and Uganda. The remaining two CxFV-positive pools were collected in Mombasa and Kakamega, far from Busia. Phylogenetic analysis revealed minimal genetic diversity among the CxFVs collected in Mombasa, Kakamega, and Busia, even though these cities are in geographically different regions. Additionally, CxFV was detected in one mosquito pool collected in Mombasa during the dry season. In addition to Culex mosquitoes, Aedes (Stegomyia) and Anopheles mosquitoes were also positive for the Flavivirus genus. Cell fusing agent virus was detected in one pool of Aedes aegypti. Mosquito flavivirus was detected in three pools of Anopheles gambiae s.l. collected in the dry and rainy seasons. Conclusions Although no mosquitoes were positive for human-related arbovirus, insect-specific viruses were detected in various species of mosquitoes. The heterogeneity observed in the number of CxFVs in Culex mosquitoes in different locations in Kenya suggests that the abundance of human-related viruses might differ depending on the abundance of insect-specific viruses. We may have underestimated the circulation of any human-related arbovirus in Kenya, and the collection of larger samples may allow for determination of the presence of human-related arboviruses.